Development of natural dye coating from anthocyanin mixed with water-based polymer / Lee Su Vei - Lee, Su Vei (2013)
In this work, anthocyanin dye extracted from roselle (Hibiscus sabdariffa L.) has been used as colourant in poly(vinyl alcohol) coating. Various additives were individually introduced into the aqueous anthocyanin. Coating was formulated by mixing the aqueous anthocyanin containing additive with PVA. Stability and properties of anthocyanin dye in aqueous as well as in coating were studied. In study of UV stability of aqueous anthocyanin, addition of hydrochloric acid enhanced UV stability of anthocyanin with a lower degradation rate of 0.0033 h-1. In study of storage stability of the aqueous anthocyanin, zinc nitrate was found to inhibit fungi growth, with no fungi colony visible and high colour stability as shown with a low total colour change (ΔE) of 13.60. Hydrochloric acid has also caused a shift in the degradation temperature to 305.37°C, considerably the highest among other samples. In UV degradation study of PVA coating, addition of acetic acid and hydrochloric acid has individually enhanced colour stability of the coating, with a total colour change of 8.95 and 16.89 respectively, lower compared to other samples. Addition of nitrate salts, on the other hand, caused a structural change in the coating. Formation of hydrogen bonding can be deduced from infrared spectroscopy. Shifts in the O-H stretching and bending, CH2, and CH3 vibrations can be observed. Increase in relative intensities of these groups due to presence of nitrate indicates hydrogen bonding between PVA and nitrate. Presence of hydrogen bonding can also be reflected on the increase in glass transition temperature of PVA samples. This indicated that the coating became glassy. Structural change in the coating was also supported by XRD study. Broadness of the diffraction halo has increased upon addition of nitrate salt. This subsequently reduced the size of the ordered domains as indicated by a shorter Scherrer column length.